Investigation of GTP-dependent dimerization of G12X K-Ras variants using ultraviolet photodissociation mass spectrometry. Issue 34 (18th July 2019) - Mehaffey, M. Rachel; Schardon, Christopher L.; Novelli, Elisa T.; Cammarata, Michael B.; Webb, Lauren J.; Fast, Walter; Brodbelt, Jennifer S.
Abstract : Variations in backbone cleavage efficiencies during UVPD-MS of G12X variants of K-Ras are used to relate mutation identity to structural changes that impact downstream signaling with Raf. Abstract : Mutations in the GTPase enzyme K-Ras, specifically at codon G12, remain the most common genetic alterations in human cancers. The mechanisms governing activation of downstream signaling pathways and how they relate back to the identity of the mutation have yet to be completely defined. Here we use native mass spectrometry (MS) combined with ultraviolet photodissociation (UVPD) to investigate the impact of three G12X mutations (G12C, G12V, G12S) on the homodimerization of K-Ras as well as heterodimerization with a downstream effector protein, Raf. Electrospray ionization (ESI) was used to transfer complexes of WT or G12X K-Ras bound to guanosine 5′-diphosphate (GDP) or GppNHp (non-hydrolyzable analogue of GTP) into the gas phase. Relative abundances of homo- or hetero-dimer complexes were estimated from ESI-MS spectra. K-Ras + Raf heterocomplexes were activated with UVPD to probe structural changes responsible for observed differences in the amount of heterocomplex formed for each variant. Holo (ligand-bound) fragment ions resulting from photodissociation suggest the G12X mutants bind Raf along the expected effector binding region (β-interface) but may interact with Raf via an alternative α-interface as well. Variations in backbone cleavage efficiencies during UV photoactivation of each variant were used to relate mutation identity to structural changes that might impact downstream signaling. Specifically, oncogenic upregulation for hydrogen-bonding amino acid substitutions (G12C, G12S) is achieved by stabilizing β-interface interactions with Raf, while a bulkier, hydrophobic G12V substitution leads to destabilization of this interface and instead increases the proximity of residues along the α-helical bundles. This study deciphers new pieces of the complex puzzle of how different K-Ras mutations exert influence in downstream signaling.